Use of an aqueous dispersion of a polymer p as a polymer binder in an electrode slurry composition for the anode of a
By using the water -based polymer scattered body prepared by free radical emulsion polymerization as a binder, the problem of fracture problems caused by the volume expansion and contraction of lithium ion secondary battery anode materials during the charging and discharge process, which improves adhesion and stability. Extend the battery life.
Patent Information
- Application Number
- CN202380042927.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-27
- Filing Date
- 2023-05-10
- Publication Date
- 2025-01-21
AI Technical Summary
The anode material of lithium-ion secondary battery is prone to breaking due to volume expansion and contraction during charging and discharging, and the adhesive content is low, making it difficult to maintain high adhesion.
An aqueous polymer dispersion prepared by free radical emulsion polymerization is used as the binder. The polymer is composed of vinyl aromatic compounds, conjugated aliphatic dienes and specific ethylenically unsaturated monomers. The polymerization temperature is 70°C. to 95°C.
Improve the adhesion and stability of the anode material in the charging and discharge cycle, extend the life of the battery, and maintain a high charging and discharge specialty.
Smart Images

Figure BDA0005153172150000091 
Figure BDA0005153172150000171 
Figure BDA0005153172150000172
Abstract
Description
[0001] The present invention relates to a method for preparing an electrode slurry composition for an anode using an aqueous polymer dispersion comprising a vinyl aromatic compound and a conjugated aliphatic diene in copolymerized form as a binder. The present invention also relates to an aqueous polymer dispersion and a method for preparing the aqueous dispersion by free radical emulsion polymerization.
[0002] Lithium-ion secondary batteries are modern devices for storing energy. Many areas of application were and are envisaged, from small devices such as mobile phones and laptops to automotive batteries and other batteries for e-mobility and energy storage. The various components of the battery such as the electrolyte, electrode materials and separators have a decisive effect on the performance of the battery. Particular attention should be paid to the electrode materials.
[0003] Generally speaking, the secondary battery using non-aqueous electrolyte solution comprises anode, cathode and non-aqueous electrolyte layer. In order to form cathode, prepare cathode slurry comprising binder, solvent and lithium transition metal oxide as cathode active material, apply this cathode slurry on collector made of metal (preferably aluminum) foil, then perform drying, pressing and molding steps.
[0004] To form the anode, the same method as above is performed except that an anode slurry containing an aqueous binder dispersion and carbon or a carbon composite or silicon or a silicon composite or silicon oxide capable of intercalating / deintercalating lithium ions as an anode active material is used.
[0005] An important requirement for lithium-ion secondary batteries is that they have good charge and discharge characteristics and therefore good life characteristics in terms of continuous AC charging processes. Charging and discharging are carried out by causing volume expansion and contraction of the anode active material by the insertion and extraction of lithium ions. Therefore, the anode, which is a composite of several materials, is exposed to strong tension, which easily leads to material fracture. In addition, the anode is required to have a high proportion and therefore also a high density of anode materials, so that the binder content is generally very low. In this regard, a binder with good adhesion is required. Although extensive research has been carried out, the solutions found so far still have room for improvement.
[0006] Thus, EP 1 058 327 describes an anode consisting of a carrier substrate and an anode active material composition, the anode active material comprising a polymer binder, a lithium intercalation compound, a conductive agent and a partially saponified acrylate / vinyl acetate copolymer. The polymer binder is a styrene / butadiene copolymer with acrylic acid and acrylamide as comonomers.
[0007] WO 2004 / 091017 describes the use of special dispersants to prepare a slurry of anode active material. The carbon in the anode is combined with a styrene / butadiene polymer.
[0008] EP 2 869 372 proposes a negative electrode slurry composition, which contains a water-soluble polymer, a negative electrode material as a combination of a silicon-based active material and a carbon-based material, and an acrylic polymer latex as a binder resin and a styrene-butadiene copolymer having a glass transition temperature of -30°C to 60°C. The styrene-butadiene copolymer latex is composed of 62 parts of styrene, 33 parts of 1,3-butadiene, 4 parts of itaconic acid and 1 part of 2-hydroxyethyl acrylate. Such polymers show insufficient strength as binders in anodes.
[0009] EP 3 007 257 discloses an elastic binder composition for secondary batteries, wherein butadiene / styrene latex particles with an average particle size in the range of 50 nm to 200 nm and acrylic copolymer latex particles with an average particle size in the range of 300 nm to 700 nm are used as binders in an electrode mixture. The butadiene content of the polymer is 60% by weight, but the strength is insufficient.
[0010] An object of the present invention is to provide a negative electrode slurry composition that can suppress the expansion of the negative electrode and maintain high adhesion to the anode active material and the current collector during repeated charge / discharge cycles. The binder polymer itself should exhibit good stress / strain behavior.
[0011] According to the invention, this object is achieved by using an aqueous dispersion of a polymer P obtainable by free radical initiated emulsion polymerization as a polymer binder in an electrode slurry composition for a secondary battery anode, the emulsion polymerization comprising polymerizing at a polymerization temperature in the range of 70° C. to 95° C.:
[0012] (a) 40 to 75 parts by weight of at least one vinyl aromatic compound,
[0013] (b) 22.5 to 55 parts by weight of at least one conjugated aliphatic diene,
[0014] (c) 0.5 to 10 parts by weight of at least one ethylenically unsaturated monomer containing an acid group
[0015] (d1) 1 to 5 parts by weight of acrylamide and / or methacrylamide,
[0016] (d2) 1 to 10 parts by weight of acrylonitrile and / or methacrylonitrile
[0017] (e) 0 to 5 parts by weight of a monoethylenically unsaturated monomer having at least one epoxy, hydroxyl, N-methylol or carbonyl group
[0018] (f) 0 to 20 parts by weight of at least one other monoethylenically unsaturated monomer,
[0019] The amounts of monomers (a) to (f) are 100 parts by weight in total.
[0020] The present invention also relates to an aqueous polymer dispersion obtainable by free radical initiated aqueous emulsion polymerization and a process for preparing the aqueous dispersion by free radical initiated emulsion polymerization, the emulsion polymerization comprising polymerizing at a polymerization temperature in the range of 70° C. to 95° C.:
[0021] (a) 40 to 75 parts by weight of at least one vinyl aromatic compound,
[0022] (b) 22.5 to 55 parts by weight of at least one conjugated aliphatic diene,
[0023] (c) 0.5 to 10 parts by weight of at least one ethylenically unsaturated monomer containing an acid group
[0024] (d1) 1 to 5 parts by weight of acrylamide and / or methacrylamide,
[0025] (d2) 1 to 10 parts by weight of acrylonitrile and / or methacrylonitrile
[0026] (e) 0 to 5 parts by weight of a monoethylenically unsaturated monomer having at least one epoxy, hydroxyl, N-methylol or carbonyl group
[0027] (f) 0 to 20 parts by weight of at least one other monoethylenically unsaturated monomer,
[0028] The amounts of monomers (a) to (f) are 100 parts by weight in total.
[0029] The present invention also relates to an electrode slurry composition for an anode comprising the polymer P, a secondary battery anode comprising the polymer P, a method for preparing the anode, and a lithium ion secondary battery comprising the anode.
[0030] Aqueous dispersions of polymers P are also referred to below as polymer dispersions. Unless stated otherwise, if amounts are reported below in parts by weight, this is based on 100 parts by weight of total monomers.
[0031] The total monomer amount is the total amount of all monomers used in the polymerization, which totals 100 parts by weight.
[0032] If the solids content of an aqueous dispersion is mentioned in % by weight, this is based on the weight of the aqueous dispersion.
[0033] In the following, the compounds derived from acrylic acid and methacrylic acid are partially shortened by inserting the syllable "(meth)" in the compounds derived from acrylic acid.
[0034] The following ethylenically unsaturated monomers (a), (b), (c), (d1), (d2), (e) and (f) can be used to prepare the aqueous polymer dispersion.
[0035] Examples of suitable vinyl aromatic compounds (monomers of group (a)) include styrene, α-methylstyrene and / or vinyltoluene. Preference is given to selecting styrene from this group of monomers.
[0036] The total amount of monomers (a) is 40 to 75 parts by weight, preferably 45 to 70 parts by weight, in particular 47 to 60 parts by weight, based on 100 parts by weight of total monomers (a to f).
[0037] Examples of conjugated aliphatic dienes (monomers of group (b)) that may be mentioned include 1,3-butadiene, isoprene, 1,3-pentadiene, dimethyl-1,3-butadiene and cyclopentadiene. Preference is given to using 1,3-butadiene and / or isoprene from this group of monomers.
[0038] The total amount of monomer (b) is 22.5 to 55 parts by weight, preferably 28 to 50 parts by weight, and in particular 32 to 45 parts by weight, based on 100 parts by weight of the total monomers.
[0039] Examples of monoethylenically unsaturated monomers (monomers (c)) containing acid groups that may be mentioned include ethylenically unsaturated carboxylic acids, ethylenically unsaturated sulfonic acids and vinylphosphonic acid. The ethylenically unsaturated carboxylic acids used are preferably α,β-monoethylenically unsaturated monocarboxylic acids and dicarboxylic acids having 3 to 6 carbon atoms in the molecule. Examples of these ethylenically unsaturated carboxylic acids are acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, vinylacetic acid and vinyllactic acid. Examples of suitable ethylenically unsaturated sulfonic acids include vinylsulfonic acid, styrenesulfonic acid, acrylamidomethylpropanesulfonic acid, sulfopropyl acrylate and sulfopropyl methacrylate. It is preferred to use acrylic acid, methacrylic acid and itaconic acid. The acids may be used as a single component or as a combination thereof.
[0040] The monomers comprising acid groups can be used in the polymerization in the form of the free acid or in a form partially or completely neutralized with a suitable base. Preference is given to using sodium hydroxide solution, potassium hydroxide solution or ammonia as neutralizing agents.
[0041] The total amount of monomers (c) is 0.5 to 10 parts by weight, preferably 1 to 8 parts by weight, in particular 2 to 5 parts by weight, of one or more monomers containing acid groups, based on 100 parts by weight of total monomers.
[0042] The total amount of monomers (d1) is 1 to 5 parts by weight, preferably 1 to 3 parts by weight, in particular 1 to 2 parts by weight of acrylamide and / or methacrylamide, preferably acrylamide, based on 100 parts by weight of total monomers.
[0043] The total amount of monomers (d2) is 1 to 10 parts by weight, preferably 1 to 8 parts by weight, in particular 1 to 7 parts by weight, of acrylonitrile and / or methacrylonitrile, preferably acrylonitrile, based on 100 parts by weight of total monomers.
[0044] The monomers (e), which usually increase the internal strength of the film-forming polymer matrix, usually have at least one epoxy, hydroxyl, N-methylol or carbonyl group. Preferred are monoethylenically unsaturated compounds having at least one N-methylol group (especially selected from the group comprising N-methylol acrylamide and N-methylol methacrylamide).
[0045] The total amount of monomers (e) is 0.1 to 5 parts by weight, preferably 0.2 to 4.5 parts by weight, in particular 0.4 to 4 parts by weight, of one or more monomers containing acid groups, based on 100 parts by weight of total monomers.
[0046] The other monoethylenically unsaturated monomers (f) are monomers which are different from the monomers of groups (a), (b), (c), (d) and (e). They are preferably selected from saturated C1 to C 18 Vinyl esters of carboxylic acids (preferably vinyl acetate) and acrylic acid and methacrylic acid with monovalent C1 to C 18 Esters of alcohols (such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-propyl acrylate, n-propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, sec-butyl acrylate, sec-butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, amyl acrylate, amyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate), allyl esters of saturated carboxylic acids, vinyl ethers, vinyl ketones, dialkyl esters of ethylenically unsaturated carboxylic acids, N-vinylpyrrolidone, N-vinylpyrrolidine, N-vinylformamide, N,N-dialkylaminoalkylacrylamide, N,N-dialkylaminoalkylmethacrylamide, N,N-dialkylaminoalkyl acrylate, N,N-dialkylaminoalkyl methacrylate, vinyl chloride and vinylidene chloride (monomers of group (f)).
[0047] This group of monomers (f) is optionally used for modification of the polymer P. The total amount of further monomers (f) can be up to 20 parts by weight, based on 100 parts by weight of total monomers. The proportion of one or more monomers of group (f), based on 100 parts by weight of total monomers, is 0 to 20 parts by weight, preferably 0.1 to 15 parts by weight, in particular 0.5 to 10 parts by weight.
[0048] Preference is given to monomers in which the vinylaromatic compound is styrene and / or methylstyrene, in particular styrene, and the conjugated aliphatic diene is 1,3-butadiene and / or isoprene, in particular 1,3-butadiene.
[0049] It is advantageous to polymerize:
[0050] (a) 45 to 68.9 parts by weight of at least one vinyl aromatic compound
[0051] (b) 28 to 50 parts by weight of at least one conjugated aliphatic diene
[0052] (c) 1 to 8 parts by weight of at least one ethylenically unsaturated carboxylic acid
[0053] (d1) 1 to 3 parts by weight, preferably 1 to 2 parts by weight, of acrylamide
[0054] (d2) 1 to 8 parts by weight, preferably 1 to 7 parts by weight, of acrylonitrile
[0055] (e) 0.1 to 4 parts by weight of a monoethylenically unsaturated monomer having at least one N-methylol group and
[0056] (f) 0 to 15 parts by weight of at least one other monoethylenically unsaturated monomer,
[0057] The amounts of monomers (a) to (f) total 100 parts by weight.
[0058] Particularly preferred is the polymerization of:
[0059] (a) 45 to 68.9 parts by weight of at least styrene
[0060] (b) 28 to 50 parts by weight of at least one 1,3-butadiene
[0061] (c) 1 to 8 parts by weight of at least one ethylenically unsaturated carboxylic acid (particularly selected from the group consisting of acrylic acid, methacrylic acid and itaconic acid)
[0062] (d1) 1 to 3 parts by weight of acrylamide
[0063] (d2) 1 to 8 parts by weight of acrylonitrile
[0064] (e) 0.1 to 4 parts by weight of a monoethylenically unsaturated monomer selected from the group consisting of N-methylol acrylamide and N-methylol methacrylamide; and
[0065] (f) 0.1 to 15 parts by weight of at least one other monoethylenically unsaturated monomer,
[0066] The amounts of monomers (a) to (f) total 100 parts by weight.
[0067] The emulsion polymerization is carried out in an aqueous medium. This can be, for example, all deionized water or a mixture of water and a solvent miscible therewith (such as methanol, ethanol, ethylene glycol, glycerol, sugar alcohols such as sorbitol or tetrahydrofuran). The total amount of aqueous medium is proportioned here so that the aqueous polymer dispersion obtained has a solids content of 20% to 70% by weight, frequently 30% to 65% by weight and often 40% to 60% by weight.
[0068] The process according to the invention uses free radical initiators (also called free radical polymerization initiators), i.e. initiators which form free radicals under the reaction conditions. These initiators can be peroxides or they can be azo compounds. Redox initiator systems are of course also suitable.
[0069] The peroxide used may in principle be an inorganic peroxide and / or an organic peroxide. Examples of suitable inorganic peroxides include hydrogen peroxide and peroxydisulfate salts, such as monoalkali metal salts or dialkali metal salts or ammonium salts of peroxydisulfate, for example their monosodium and disodium, monopotassium and dipotassium or ammonium salts. Examples of suitable organic peroxides are alkyl hydroperoxides such as tert-butyl hydroperoxide; aryl hydroperoxides such as p-menthyl or isopropylbenzene hydroperoxide; and dialkyl or diaryl peroxides such as di-tert-butyl, dibenzoyl or diisopropylbenzene peroxides.
[0070] The azo compounds used are essentially 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(N,N'-dimethyleneisobutyramidine) dihydrochloride and 2,2'-azobis(amidinopropyl) dihydrochloride (AIBA, corresponding to V-50 from Wako Chemicals).
[0071] Redox initiator systems are combined systems consisting of at least one organic or inorganic reducing agent and at least one peroxide. Suitable oxidizing agents for redox initiator systems are essentially the peroxides mentioned above. Corresponding reducing agents that can be used are sulfur compounds in a low oxidation state, such as alkali metal sulfites, for example potassium sulfite and / or sodium sulfite; alkali metal bisulfites, for example potassium bisulfite and / or sodium bisulfite; alkali metal metabisulfites, for example potassium metabisulfite and / or sodium metabisulfite; acetone bisulfite; formaldehyde bisulfite, for example potassium formaldehyde bisulfite and / or sodium formaldehyde bisulfite; alkali metal salts, in particular potassium and / or sodium salts of aliphatic sulfinic acids and alkali metal hydrogensulfides, for example potassium hydrogensulfide and / or sodium hydrogensulfide; salts of polyvalent metals, such as iron(II) sulfate, ammonium iron(II) sulfate, iron(II) phosphate; enediols, such as dihydroxymaleic acid, benzoin and / or ascorbic acid; and reducing sugars, such as sorbitol, glucose, fructose and / or dihydroxyacetone.
[0072] Preferred free radical initiators are inorganic and organic peroxides, preferably ammonium or alkali metal persulfates or peroxodisulfates, and tert-butyl, p-menthyl and cumyl hydroperoxides, in particular selected from sodium and potassium peroxodisulfates, tert-butyl hydroperoxide and cumyl hydroperoxide. Particular preference is given here to the use of both at least one inorganic peroxide, preferably peroxodisulfate, in particular sodium peroxodisulfate, and / or one organic peroxide, preferably an alkyl hydroperoxide, in particular tert-butyl hydroperoxide.
[0073] The polymerization is generally carried out using 0.1 to 5 parts by weight, preferably 0.5 to 4 parts by weight, of free radical initiator, based on 100 parts by weight of total monomers.
[0074] Initiation of the polymerization reaction is understood to mean that the polymerization reaction of the monomers present in the polymerization vessel begins as a result of the decomposition of the free-radical initiator.
[0075] Preferably, the process of the present invention is a monomer feed process.Monomer feed process means that a major amount (usually at least 90%, preferably at least 93%) of the monomer to be polymerized is supplied to the polymerization reaction under polymerization conditions.
[0076] Here it is possible to include a portion of the monomers in the initial charge in the polymerization vessel before the start of the polymerization. Then, according to this preferred variant, the polymerization can be initiated in an initial charge containing 1 to 10 parts by weight of the total monomers, and then the monomers and emulsifiers are metered continuously. More particularly, it is possible to include up to 5% of the corresponding monomers in the initial charge and then initiate the polymerization.
[0077] Polymerization conditions generally refer to the amount of free radical initiator and the temperature and pressure at which the free radical initiated aqueous emulsion polymerization does not stop. The polymerization here depends mainly on the nature and amount of the free radical initiator used. For common polymerization initiators, the relationship between temperature and decomposition rate is well known to those skilled in the art or can be determined in routine experiments.
[0078] According to a preferred embodiment, the monomers and the emulsifiers are metered continuously. In other words, the monomer metering and the emulsifier metering are carried out in a continuous mass flow, ie without interruption.
[0079] According to the present invention, the polymerization is carried out in a temperature range of 70°C to 95°C, preferably ≥75°C to ≤90°C.
[0080] The metering of the conjugated aliphatic diene is usually carried out under high pressure. The metering of the conjugated aliphatic diene is preferably carried out at a pressure in the range from 5 bar to 15 bar. The high pressure has the effect that, for example, 1,3-butadiene, which is gaseous at standard pressure and room temperature, is mostly present in the polymerization mixture.
[0081] Preference is given to continuous metering, i.e. uninterrupted metering of the monomers. In this case, preference is given to metering the monomers at a metering rate which deviates by no more than 30%, preferably by no more than 20%, from the average value of the corresponding total feed. According to a preferred embodiment, the metering rate of the monomers (increase in monomers) corresponds approximately to the polymerization rate of the monomers (reduction in monomers).
[0082] To promote the emulsification of the monomers in the aqueous medium, commonly used protective colloids and / or emulsifiers can be used. A detailed description of suitable protective colloids can be found in Houben-Weyl, Methoden der organischen Chemie [Methods of Organic Chemistry], Volume XIV / 1, Makromolekulare Stoffe [Macromolecular Materials], Georg-Thieme-Verlag, Stuttgart, 1961, pages 411 to 420.
[0083] Useful emulsifiers include interface-active substances having a number average molecular weight of generally less than 2000 g / mol or preferably less than 1500 g / mol, and protective colloids having a number average molecular weight of more than 2000 g / mol, for example 2000 g / mol to 100 000 g / mol, in particular 5000 g / mol to 50 000 g / mol. Suitable emulsifiers are described in WO 2020 / 114798, page 9, line 40 to page 10, line 22.
[0084] If emulsifiers and / or protective colloids are additionally used as auxiliaries for dispersing the monomers, they are used in amounts of, for example, 0.1 to 5 parts by weight, based on 100 parts by weight of monomers.
[0085] Commonly used emulsifiers are, for example, ethoxylated mono-, di- and tri-alkylphenols (EO level: 3 to 50, alkyl group: C4 to C 12 ), ethoxylated fatty alcohols (EO level: 3 to 50; alkyl groups: C8 to C 36 ) and alkyl sulfates (alkyl groups: C8 to C 12 ) alkali metal and ammonium salts, ethoxylated alkanols (EO level: 3 to 30, alkyl group: C 12 To C 18 ) and ethoxylated alkylphenols (EO level: 3 to 50, alkyl group: C4 to C 12 ) of alkali metal and ammonium salts of sulfuric acid monoesters, alkylsulfonic acids (alkyl group: C 12 To C 18 ) alkali metal salts and ammonium salts, and alkyl aryl sulfonic acids (alkyl group: C9 to C 18 ) alkali metal salts and ammonium salts of . Other suitable emulsifiers can be found in Houben-Weyl, Methoden der organischen Chemie [Methods of Organic Chemistry], Volume XIV / 1, Makromolekulare Stoffe [Macromolecular substances], pages 192-208, Georg-Thieme-Verlag, Stuttgart, 1961.
[0086] Other suitable surface-active substances have been found to be compounds of the general formula I
[0087]
[0088] Where R 1 and R 2 C4 to C 24 Alkyl and R 1 and R 2 One of the groups may also be hydrogen, and A and B may be alkali metal ions and / or ammonium ions. 1 and R 2 Preferably, it is a straight-chain or branched alkyl group having 6 to 18 carbon atoms, in particular 6, 12 or 16 carbon atoms, or a hydrogen atom, wherein R 1 and R 2A and B are preferably sodium ions, potassium ions or ammonium ions, and particularly preferably sodium ions. Particularly advantageous compounds I are those in which A and B are sodium ions, R 1 is a branched alkyl group having 12 carbon atoms and R 2 is a hydrogen atom or R 1 Frequently, technical-grade mixtures containing monoalkylated products in proportions of 50 to 90% by weight are used, for example 2A1 (trademark of the Dow Chemical Company). Compound I is well known, for example from US Pat. No. 4,269,749, and is commercially available.
[0089] If dispersing aids are included in the preparation of the aqueous dispersion of polymer P, the total amount of dispersing aids, especially emulsifiers, used is 0.1% to 5% by weight, preferably 1% to 3% by weight, in each case based on the total amount of monomers. In an advantageous embodiment, an emulsifier is used as the only dispersing aid.
[0090] If a dispersing aid is included in the preparation of the aqueous dispersion of polymer P, a portion or all of the dispersing aid may optionally be charged initially as a component of the aqueous medium comprising polymer A. Alternatively, all or any remaining residual amounts of dispersing aid may be metered during the polymerization reaction together with the monomers P. The manner in which all or any remaining residual amounts of dispersing aid are metered into the aqueous polymerization medium may be discontinuous in one or more portions or continuous with a constant or varying flow rate.
[0091] According to one embodiment of the present invention, the polymerization is carried out in the presence of degraded starch. In the emulsion copolymerization, it is preferred to use 15 to 100 parts by weight of degraded starch per 100 parts by weight of monomer.
[0092] Degraded starch is generally known and is described, for example, in WO 2020 / 249406, page 15 to page 16, line 2.
[0093] Preferred are degraded native starches, in particular native starches degraded to maltodextrins.
[0094] Preference is given to degraded starches having an intrinsic viscosity ηi≤0.07 dl / g or preferably ≤0.05 dl / g. The intrinsic viscosity ηi of the degraded starch is preferably in the range of 0.02 dl / g to 0.06 dl / g. The intrinsic viscosity ηi is determined according to DIN EN 1628 at a temperature of 23°C.
[0095] According to a further preferred embodiment, no degraded starch is present during the polymerisation.
[0096] In addition to the seedless preparation mode, the polymer particle size can also be adjusted by the seed latex method or by carrying out the emulsion polymerization in the presence of an in situ prepared seed latex for preparing the polymer P. Such methods are known to those skilled in the art and can be found in the prior art (see, for example, EP-B 40419, EP-A 567 812, EP-A 614 922 and "Encyclopedia of Polymer Science and Technology", Volume 5, page 847, John Wiley & Sons Inc., New York, 1966).
[0097] According to a preferred variant of the emulsion polymerization process, a seed latex is used.
[0098] The so-called "seed latex" is generally understood by those skilled in the art to be a polymer dispersion whose seed particles serve as nuclei for particle formation during the polymerization process.
[0099] According to a preferred process variant, an aqueous polymer dispersion having a weight-average particle size Dw50 in the range from 20 nm to 60 nm and a Dw50 / Dn50 ratio ≤2 is used as seed latex.
[0100] In the following, the weight average particle size is understood to mean the weight average Dw50 value determined by the analytical ultracentrifugation method, and the number average Dn50 value determined by the same method is understood to mean the average particle size (see SE Harding et al., Analytical Ultracentrifugation in Biochemistry 5 and Polymer Science, Royal Society of Chemistry, Cambridge, Great Britain 1992, Chapter 10, Analysis of Polymer Dispersions with an Eight-Cell-AUC-Multiplexer: High Resolution Particle Size Distribution and Density Gradient Techniques, W. Pages 147 to 175). In the context of the present specification, a narrow particle size distribution is understood if the ratio of the weight-average particle size Dw50 to the number-average particle size Dn50 [Dw50 / Dn50] determined by the analytical ultracentrifugation method is less than or equal to 2.0, preferably less than or equal to 1.5, particularly preferably less than or equal to 1.2 or less than or equal to 1.1.
[0101] The preparation of seed latex is known to the person skilled in the art and is usually carried out in the presence of large amounts of emulsifiers, which results in small particle sizes and narrow particle size distributions. It is generally observed that, in contrast to in situ seed latexes, polymerizations carried out in the presence of such exogenous seed latexes are characterized by uniform particle growth. Seed latexes, as the name implies, are usually used in the form of aqueous dispersions.
[0102] The seed latex is preferably a styrene polymer and / or a methyl methacrylate polymer having a glass transition temperature of ≥50° C., ≥60° C., ≥70° C., ≥80° C. or ≥90° C., measured in accordance with DIN EN ISO 11357-2 (2013-09).
[0103] Preferably, 0.01 to 3 parts by weight, in particular 0.02 to 1 part by weight, of seed latex (calculated as solids), based on the total monomers, is used.
[0104] Preferably, polymerization is initiated in an initial charge in the polymerization vessel containing up to 3 parts by weight of an aqueous dispersion of polystyrene seed latex, based on 100 parts by weight of total monomers, followed by continuous addition of monomers and emulsifiers in doses.
[0105] In order to modify the properties of the polymer, the emulsion polymerization can optionally be carried out in the presence of at least one free radical chain transfer agent, particularly preferably a sulfur-, nitrogen- and / or phosphorus-containing free radical chain transfer agent having a solubility of ≥5 g / 100 g in deionized water at 20° C. and 1 atm. These free radical chain transfer agents are generally used to reduce or control the molecular weight of the polymers obtainable by free radical aqueous emulsion polymerization.
[0106] The sulfur-containing free radical chain transfer agents used are, for example: alkyl mercaptans such as n-hexyl mercaptan, n-octyl mercaptan, tert-octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan and n-stearyl mercaptan; mercaptoalkanols such as 2-mercaptoethanol, 2-mercaptopropanol or 3-mercaptopropanol; alkyl esters of thioglycolic acid such as 2-ethylhexyl thioglycolate; alkyl esters of 3-mercaptopropionic acid such as isooctyl mercaptopropionate; alkali metal bisulfites such as sodium bisulfite or hydrogen sulfite and thiosulfate and its alkali metal salts or 3-mercapto-2-aminopropionic acid (cysteine), the nitrogen-containing free radical chain transfer agents used are, for example, hydroxylamine (ammonium) compounds such as hydroxylammonium sulfate, the phosphorus-containing free radical chain transfer agents used are, for example, phosphorous acid, hypophosphorous acid, metaphosphorous acid, orthophosphoric acid, pyrophosphoric acid or polyphosphoric acid and their alkali metal salts (especially their sodium or potassium salts, advantageously sodium hypophosphite or sodium dihydrogen phosphate), and thiuram-based compounds such as terpinolene.
[0107] Particularly advantageously, the free-radical chain transfer agent is selected from the group consisting of hypophosphorous acid and its alkali metal salts (especially sodium hypophosphite), alkali metal hydrogen sulfites (especially sodium hydrogen sulfite), hydroxylammonium sulfate and / or 2-mercaptoethanol, tert-dodecyl mercaptan and terpinolene.
[0108] According to a preferred embodiment, the amount of the free radical chain transfer agent used in the polymerization is ≤ 1 part by weight, preferably in the range of 0.1 to 1 part by weight, preferably in the range of 0.2 to 0.8 parts by weight, based on 100 parts by weight of the total monomers used in the polymerization.
[0109] In order to complete the polymerization, it is in most cases sufficient to stir the reaction mixture at the polymerization temperature, for example for a further 0.2 hour to 3 hours after all the monomers have been added. A conversion of about 95% has generally been achieved by this time.
[0110] To further increase the conversion, it is possible, for example, to add further free radical initiators from the abovementioned initiators to the reaction mixture or to prolong the addition and the so-called "postpolymerization" (ie polymerization to a conversion of >95% up to 99%).
[0111] This postpolymerization can be carried out at the same, lower or higher temperature than the main polymerization. For example, based on 100 parts by weight of the monomers used for the polymerization, 0.1 to 1.5 parts by weight of an inorganic peroxide (preferably sodium peroxodisulfate) is metered in at this stage as an initiator, and the polymerization temperature is set to a temperature in the range of 70° C. to 95° C.
[0112] The pH during the polymerization may be, for example, from 1 to 5. After the end of the polymerization at a conversion of >95%, the pH is adjusted, for example, to a value between 6 and 7.
[0113] In addition, chemical deodorization can also be carried out. If traces of residual monomers are still to be removed, this can also be achieved chemically by the action of redox initiator systems, as described in DE-A 44 35 423, DE-A 44 19 518 and DE-A 44 35 422. Suitable oxidizing agents are in particular the above-mentioned organic and / or inorganic peroxides. Suitable reducing agents preferably include sodium disulfite, sodium bisulfite, sodium dithionite, sodium hydroxymethanesulfinic acid, formamidinesulfinic acid, acetone bisulfite (= addition product of sodium bisulfite on acetone), ascorbic acid or reducing sugar compounds, or water-soluble mercaptans such as mercaptoethanol.
[0114] The treatment with the redox initiator system is carried out in a temperature range of 60° C. to 100° C., preferably 70° C. to 90° C. The redox partners can be added to the dispersion individually, either in their entirety, in batches or continuously over a period of 10 minutes to 4 hours. In order to improve the postpolymerization of the redox initiator system, soluble salts of metals of different valence, such as iron, copper or vanadium salts, can be added to the dispersion. Complexing agents are also frequently added which keep the metal salts in solution under the reaction conditions.
[0115] After the polymerization reaction (main polymerization + postpolymerization) and optional chemical deodorization, it may be necessary to make the aqueous polymer dispersion substantially free of odor carriers such as residual monomers and other volatile organic components, which is also referred to as physical deodorization. This can be achieved in a manner known per se by physical means by distillative removal (in particular via steam distillation) or by stripping with an inert gas.
[0116] According to the invention, the aqueous dispersion of polymer P is used as polymer binder in an electrode slurry composition for anodes of secondary batteries.
[0117] It is preferred that the polymer P has a value of at least 8 N / mm 2 , preferably 8N / mm 2 Up to 20N / mm 2 The breaking stress is within the range and the strain is at least 150%.
[0118] The present invention also relates to an electrode slurry composition for an anode, which comprises a polymer P, an anode active material, a conductive material, a co-binder and a dispersion medium.
[0119] The proportion of the polymer P in the electrode slurry composition for anode is in the range of 0.5 to 20 wt %, preferably 0.7 to 10 wt %, based on the electrode slurry composition for anode, both based on the solid content.
[0120] The anode active material may be any material capable of intercalating lithium.
[0121] Preferred anode active materials are silicon, silicon oxide, graphite, silicon-carbon composites, tin, lithium, aluminum, lithium titanium oxide and lithium silicon. Particularly preferred are graphites such as artificial graphite, natural graphite and fiber graphite as well as silicon, silicon oxide and silicon-carbon composites.
[0122] The amount of the anode active material in the electrode slurry composition for anode ranges from 50 to 98 wt %, preferably 75 to 98 wt %, based on the electrode slurry composition for anode, both based on solid content.
[0123] The conductive material may be any one selected from the group consisting of carbon black, acetylene black, carbon fiber, multi-walled carbon nanotube, single-walled carbon nanotube, Ketjen black, and a mixture thereof.
[0124] The amount of the conductive material in the electrode slurry composition for anode ranges from 0.01 to 20 wt %, preferably 0.02 to 10 wt %, based on the electrode slurry composition for anode, both based on solid content.
[0125] The co-binder is a water-soluble polymer, which can be any one selected from the group consisting of methylcellulose, carboxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, ethylhydroxyethylcellulose, hydroxyalkylmethylcellulose, polyvinyl alcohol, polyvinylpyrrolidone, polyvinylpyridine, polyacrylonitrile, polyethylene oxide and mixtures thereof. Preferred co-binders are selected from the group consisting of methylcellulose, carboxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, ethylhydroxyethylcellulose and hydroxyalkylmethylcellulose.
[0126] The amount of the co-binder is in the range of 0.5 wt % to 20 wt %, preferably 0.7 wt % to 5 wt % of the electrode slurry composition for the anode (all calculated as solids).
[0127] The dispersion medium may be any one selected from the group consisting of acetone, dimethylformamide, N-methyl-2-pyrrolidone, tetrahydrofuran, isopropanol, ethanol, methanol and water and mixtures thereof. Water is preferably used as the dispersion medium. The amount of the dispersion medium in the slurry containing the anode active material is in the range of 20 wt % to 70 wt %, preferably 30 wt % to 60 wt %.
[0128] It is preferred that the electrode slurry composition for an anode comprises a dispersion medium and
[0129] 0.5 to 20% by weight of polymer P,
[0130] 50 wt % to 98 wt % of anode active material,
[0131] 0.01 wt % to 20 wt % of a conductive material,
[0132] 0.5 wt % to 20 wt % co-binder.
[0133] In addition, according to another aspect of the present disclosure, an anode is provided, which includes a current collector; and an anode active material composition layer, which is formed by coating the above-mentioned electrode slurry (for example, by slot extrusion, dipping, reverse roller, direct roller, concave coating, extrusion, doctor blade, dipping, brushing or dipping) on one or both surfaces of the current collector, and then drying.
[0134] Non-limiting examples of current collectors may include foils obtained from copper, gold, nickel, aluminum, copper-containing alloys, or combinations thereof.
[0135] The present invention also relates to a method for preparing a secondary battery anode, the method comprising the following steps:
[0136] (a) combining an aqueous dispersion of polymer P, an anode active material, a conductive material, a co-binder and a dispersion medium into an electrode slurry composition
[0137] (b) Providing a current collector
[0138] (c) Coating the current collector with the electrode slurry composition
[0139] (d) drying the coated collector and
[0140] (e) optionally molding the dried coated collector.
[0141] Drying may comprise one or more drying steps carried out at a temperature ranging from 20°C to 300°C, preferably at a temperature ranging from 50°C to 150°C. The drying step results in the removal of the dispersion medium. Drying is generally performed until a constant weight is reached.
[0142] Preferably, the dried coated collector is molded. The molding is performed according to conventional methods known in the art. Non-limiting examples of molding devices are calenders or presses.
[0143] As used herein, "molded collector" means a dried coated collector that has been molded and has pores inside. The porosity of the molded collector is preferably 10% to 60%. Because the expansion and contraction of the negative electrode active material during charge / discharge can be absorbed and reduced, the negative electrode must maintain its shape. More preferably, the porosity is 30% to 50%. The porosity can be controlled by changing the conditions for preparing the molded collector. For example, when a molded collector is prepared by applying pressure on a dried coated collector, the compression force can be adjusted to control the porosity. The porosity can be calculated using the volume V1 determined by the size of the resulting molded article and the absolute volume V0 of the molded article, and is represented by {(V1-V0) / V1}×100(%).
[0144] The coating amount of the dried electrode slurry composition for the anode is 10 g / m2 Collector foil up to 300g / m 2 Collector foil, preferably 25 g / m 2 Collector foil up to 200g / m 2 within the range of the collector foil.
[0145] The present invention also relates to a secondary battery anode formed by applying the electrode slurry composition for an anode to a current collector and drying the negative electrode slurry composition. The present invention also relates to a lithium ion secondary battery including the secondary battery anode.
[0146] The cathode used in the secondary battery is not particularly limited and may be manufactured by bonding a cathode active material to a current collector according to a conventional method known in the art.
[0147] As cathode active materials, those materials commonly used in secondary battery cathodes can be used. Non-limiting examples of cathode active materials may include lithium-manganese oxide, lithium-cobalt oxide, lithium-nickel oxide, lithium-iron oxide, and combinations thereof. In addition, non-limiting examples of current collectors for cathodes may include foils obtained from iron, aluminum, copper, nickel, or combinations thereof. Such cathode active materials are described, for example, in WO 2021 / 078626.
[0148] The separator that can be used for the secondary battery includes any separator that has been conventionally used in the art, such as a porous film or nonwoven fabric made of a polyolefin-based polymer, and is described, for example, in WO 2021 / 078626, page 10. The separator preferably has a thickness of, but not limited to, 5 μm to 50 μm. In addition, the separator has a pore size of 30 nm to 750 nm and a porosity of 10% to 95%, but is not particularly limited thereto.
[0149] In order to improve the mechanical strength of the separator and the safety of the secondary battery, a porous coating comprising inorganic particles and a polymer binder may be further formed on at least one surface of the separator. The inorganic particles are not particularly limited as long as they are electrochemically stable. That is, within the operating voltage range of the applied secondary battery (e.g., based on Li / Li + 0V to 5V) no redox reaction occurs.
[0150] In addition, a secondary battery is provided, which includes a cathode, an anode according to the present invention, a separator interposed between the cathode and the anode, and a non-aqueous electrolyte. In particular, among the secondary batteries, lithium secondary batteries (including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries or lithium ion polymer secondary batteries) are preferred.
[0151] The assembly can be performed by laminating, stacking or folding the separator and the electrode and winding method. The resulting assembly is rolled up or bent according to the shape of the battery and placed in a battery container, and the electrolyte solution is injected into the battery container and the battery container is sealed. In addition, the shape of the secondary battery is not limited. For example, the shape of the battery can be like a coin, a button or a pouch, and can be cylindrical, prismatic, square or flat. In addition, the shape of the secondary battery is not limited.
[0152] The electrolyte solution used in the present disclosure contains a lithium salt as an electrolyte salt. The lithium salt may be any lithium salt conventionally used in an electrolyte solution for a lithium secondary battery. Examples of suitable lithium salts are LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC(C n F 2n+1 SO2)3, lithium imide such as LiN(C n F 2n+1 SO2)2 (wherein n is an integer in the range of 1 to 20), LiN(SO2F)2, Li2SiF6, LiSbF6, LiAlCl4 and the general formula (C n F 2n+1 SO2) t A salt of YLi, wherein m is defined as follows:
[0153] When Y is selected from oxygen and sulfur, t=1;
[0154] When Y is selected from nitrogen and phosphorus, t=2; and
[0155] When Y is selected from carbon and silicon, t=3.
[0156] Preferred electrolyte salts are selected from LiC(CF3SO2)3, LiN(CF3SO2)2, LiPF6, LiBF4, LiClO4, among which LiPF6 and LiN(CF3SO2)2 are particularly preferred.
[0157] The electrolyte solution used in the present disclosure comprises an organic solvent conventionally used in the electrolyte solution of a lithium secondary battery. For example, the solvent used for the electrolyte may be liquid or solid at room temperature, and is preferably selected from cyclic or acyclic ethers, cyclic and acyclic acetals, and cyclic or acyclic organic carbonates.
[0158] In addition, the electrolyte solution may contain a thickener such as a polyalkylene glycol, preferably a polyC1-C4 alkylene glycol, in particular polyethylene glycol. The polyethylene glycol may contain up to 20 mol % of one or more C1-C4 alkylene glycols. The polyalkylene glycol is preferably a polyalkylene glycol with two methyl or ethyl end caps.
[0159] The molecular weight M of suitable polyalkylene glycols, in particular suitable polyethylene glycols, isw The molecular weight M of suitable polyalkylene glycols, in particular suitable polyethylene glycols, may be at least 400 g / mol. w It may be at most 5 000 000 g / mol, preferably at most 2 000 000 g / mol.
[0160] Examples of suitable acyclic ethers are, for example, diisopropyl ether, di-n-butyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, preference being given to 1,2-dimethoxyethane.
[0161] Examples of suitable cyclic ethers are tetrahydrofuran and 1,4-dioxane.
[0162] Examples of suitable acyclic acetals are, for example, dimethoxymethane, diethoxymethane, 1,1-dimethoxyethane and 1,1-diethoxyethane.
[0163] An example of a suitable cyclic acetal is 1,3-dioxane, in particular 1,3-dioxolane.
[0164] Examples of suitable acyclic organic carbonates are dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate.
[0165] Examples of suitable cyclic organic carbonates are compounds according to formula (II) and (III)
[0166]
[0167] Where R 1 , R 2 and R 3 may be the same or different and are selected from hydrogen and C1-C4 alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl, wherein R 2 and R 3 Preferably, they are not tert-butyl at the same time.
[0168] In a particularly preferred embodiment, R 1 is methyl and R 2 and R 3 Each is hydrogen, or R 1 , R 2 and R 3 Each is hydrogen.
[0169] Another preferred cyclic organic carbonate is vinylene carbonate, formula (IV).
[0170]
[0171] The solvent or solvents are preferably used in anhydrous state, ie wherein the water content is in the range from 1 ppm to 0.1% by weight, as can be determined, for example, by Karl Fischer titration.
[0172] The polymer P according to the present invention has high adhesion to the surface of the anode active material, the solid electrolyte interface (SEI) formed on the anode active material during the first charge, and also to the copper foil as a collector. In addition, the polymer P acts as a binder to maintain the adhesion between the anode active material and the collector during the charge / discharge cycle of the battery. Charging and discharging are carried out by causing the volume expansion and contraction of the anode active material through the insertion and extraction of lithium ions. This may weaken the adhesion of the polymer binder during repeated charge and discharge cycles, thereby damaging the conductive structure of the electrochemical device. Therefore, the charge and discharge characteristics and life characteristics such as battery capacity are reduced.
[0173] The accumulator according to the invention exhibits, for example, good discharge behavior at low temperatures (0° C. or lower, for example down to −10° C. or even lower), very good discharge and cycling behavior.
[0174] The battery according to the invention may comprise two or more electrochemical cells which are combined with each other, for example connected in series or in parallel. A series connection is preferred. In the battery according to the invention, at least one of these electrochemical cells contains at least one anode according to the invention. Preferably, in the electrochemical cell according to the invention, the majority of the electrochemical cells contain an anode according to the invention. Even more preferably, in the battery according to the invention, all electrochemical cells contain an anode according to the invention.
[0175] The invention also relates to the use of a battery according to the invention in an appliance, in particular in a mobile appliance. Examples of mobile appliances are vehicles such as cars, bicycles, airplanes, or water vehicles such as boats or ships. Other examples of mobile appliances are those that are moved manually, such as computers, in particular laptops, telephones or (for example in the construction industry) electric hand tools, in particular drills, battery-operated screwdrivers or battery-operated stitchers. Example
[0176] Unless the context indicates otherwise, percentages always refer to percentages by weight. The reported contents relate to the contents in aqueous solution or dispersion. The expression "pphm (parts per hundred monomer)" denotes the proportion by weight based on 100 parts by weight of monomer.
[0177] Where water was used in the context of the examples, deionized water was used.
[0178] Measurement method
[0179] granularity :
[0180] Analytical ultracentrifugation (AUC)
[0181] The size and size distribution of particles in polymer dispersions were determined using analytical ultracentrifugation (AUC) with turbidity-based optics and Mie correction for the transmitted intensity of each size. All components with diameters from 30 nm to 5 μm were measured using turbidity detection.
[0182] The method uses a uniform initial sedimentation. The method is carried out according to the guidelines of ISO 13318-1, where the specific setup is described in W. L. Chapter 3 of "Analytical Ultracentrifugation of Polymers and Nanoparticles", Springer Science and Business Media, Berlin 2006. The evaluation starts with the spherical morphology of the solid particles, which is determined by the comonomer composition. The results are reported as a volume measure expressed as the sphere equivalent diameter.
[0183] For the measurement, the dispersion was diluted to a concentration of 4 g (solid) / liter with 0.05 wt% aqueous surfactant solution and measured under the same conditions. The weight fraction of the particle population is obtained directly from the integration of the measurement results.
[0184] Hydrodynamic Chromatography (HDC)
[0185] The size and size distribution of particles in polymer dispersions are also determined using hydrodynamic chromatography (HDC). HDC is a liquid chromatography technique that separates analytes based on their size in solution. Measurements are made using a PL-PSDA particle size distribution analyzer (Polymer Laboratories, Inc.). A small amount of polymer latex sample is injected into an aqueous eluent containing an emulsifier to give a concentration of about 0.5 g / l. The mixture is pumped through a glass capillary of about 15 mm diameter filled with polystyrene balls. As determined by their hydrodynamic diameter, smaller particles can spatially enter slower flowing regions in the capillary, so that on average smaller particles experience a slower elution flow. The classification is finally monitored using a UV detector that measures extinction at a fixed wavelength of 254 nm.
[0186] Solid content :
[0187] The solid content of the polymer dispersion is determined as follows: 0.5 g to 1.5 g of the polymer dispersion is distributed in a metal cover with a diameter of 4 cm and then dried in a forced air drying cabinet at 140° C. for 30 minutes. The ratio of the mass of the sample after drying under the above conditions to the mass at the time of sampling gives the solid content of the polymer dispersion.
[0188] Glass transition temperature T g
[0189] The glass transition temperature is determined according to DIN 53765 using a DSC820 instrument of the TA8000 series from Mettler-Toledo Int. Inc.
[0190] The starting materials used in the examples are as follows:
[0191] Emulsifier A: Sodium lauryl sulfate (from BASF) in the form of a 15 wt% solution SDS
[0192] Emulsifier B: 45 wt% sodium dodecyl diphenyl ether disulfonate
[0193] Complexing agent: EDTA in the form of a 2 wt% solution (from BASF BX)
[0194] Seed latex: 29.7 wt% polystyrene seeds with a particle size of 30 nm (determined by analytical ultracentrifugation) in the form of a dispersion
[0195] Initiator A: 7 wt% sodium persulfate (NaPS) solution
[0196] Initiator B: 10 wt% tert-butyl hydroperoxide solution
[0197] Reducing agent: 13 wt% acetone bisulfite solution
[0198] Unless otherwise stated, water was deionized. In all examples, feeds were metered at a uniform volumetric flow rate.
[0199] Preparation of emulsion polymer
[0200] Amounts expressed below in pphm (parts per hundred monomer) are based on 100 parts by weight of total monomers.
[0201] Example 1 - Binder 1
[0202] Initial feed :
[0203] 339.56g of water
[0204] 14.48 g of a 29.7 wt% dispersion of polystyrene latex with an average particle size of 30 nm (0.20 pphm)
[0205] 3.01 g of acrylic acid (0.14 pphm)
[0206] 184.29 g of 7 wt% aqueous itaconic acid solution (0.6 pphm)
[0207] 32.25 g of 2 wt% EDTA solution (complexing agent) (0.03 pphm)
[0208] 2.15 g of 50 wt% acrylamide solution (0.05 pphm)
[0209] 1.43 g of 15 wt% sodium lauryl sulfate solution (emulsifier A) (0.01 pphm)
[0210] 4.30 g of 45 wt% sodium dodecyl diphenyl ether disulfonate (emulsifier B) (0.09 pphm)
[0211] 43.00 g of styrene (2.0 pphm)
[0212] 21.50 g of butadiene (1.0 pphm)
[0213] Add 1 :
[0214] 61.43 g of 7 wt% sodium peroxodisulfate solution (Initiator A) (0.20 pphm)
[0215] Feed 1 :
[0216] 55.04 g of 50 wt% acrylamide solution (1.28 pphm)
[0217] 34.40 g of 15 wt% sodium lauryl sulfate solution (0.24 pphm)
[0218] 24.84 g of 45 wt% sodium dodecyl diphenyl ether disulfonate (emulsifier B) (0.52 pphm)
[0219] 35.83 g of 15 wt% sodium hydroxide solution (0.25 pphm)
[0220] 715.72ml of water
[0221] Feed 2 :
[0222] 71.81 g of acrylic acid (3.34 pphm)
[0223] 1070.27 g of styrene (49.78 pphm)
[0224] 107.5 g of acrylonitrile (5.0 pphm)
[0225] 8.60 g of tert-dodecyl mercaptan (0.4 pphm)
[0226] Feed 3 :
[0227] 791.42 g of butadiene (36.81 pphm)
[0228] Feed 4 :
[0229] 251.86 g of 7 wt% sodium peroxodisulfate solution (0.82 pphm)
[0230] Feed 5 :
[0231] 75.25 g of 10 wt% tert-butyl hydroperoxide (Initiator B) solution (0.35 pphm)
[0232] Feed 6 :
[0233] 80.82 g of 13.1 wt% acetone bisulfite solution (0.53 pphm)
[0234] Feed 7 :
[0235] 104.63 g of 15 wt% sodium hydroxide solution (0.73 pphm)
[0236] The components of the initial charge were charged to a 6 l pressure reactor and mixed. The initial charge was heated to 85° C. When 85° C. was reached, initiator A (charge 1) was added within 5 minutes and polymerization was started. The mixture was stirred for a further 5 minutes.
[0237] Feeds 1, 2, 3 and 4 were then started immediately (time: 0 minutes) and the temperature was continuously reduced to 80° C. over a period of 20 minutes. Feeds 1, 2 and 4 were completed over a period of 6 hours. Feed 3 was completed over a period of 5 hours and 30 minutes.
[0238] After the end of the metered addition of feeds 1, 2 and 4, the polymerization mixture was stirred for a further 30 minutes. 308.1 ml of water (14.33 pphm) were then added.
[0239] Feeds 5 and 6 were then started and completed over a period of 90 minutes. Feed 7 was started 15 minutes before the end of feeds 5 and 6 and completed over a period of 15 minutes. After the end of feeds 5, 6 and 7, the polymerization mixture was cooled to room temperature.
[0240] The solid content of the dispersion was 50.5% by weight. The glass transition temperature T g It is 7.2℃.
[0241] Analysis of polymer dispersions using HDC:
[0242] Particle size distribution: The maximum peak is at 268nm with a tail.
[0243] Example 2-10 Binder 2-10
[0244] Analogously to Example 1, further dispersions were prepared using the monomer compositions given in Table 1.
[0245] Example 2 - Binder 2 (not according to the invention)
[0246] Emulsion polymerization was carried out as described in Example 1 of the present invention, except that feed 2 did not contain acrylonitrile, and the styrene content in feed 2 was increased.
[0247] The solid content of the dispersion was 50.5% by weight. The glass transition temperature T g is 2℃.
[0248] Analysis of polymer dispersions using HDC:
[0249] Bimodal particle size distribution:
[0250] The particle population of "smaller" particles has its maximum peak at 271 nm and the proportion of the total polymer is 96% by weight.
[0251] The particle population of "larger" particles has its maximum peak at 468 nm and the proportion of the total polymer is 4% by weight.
[0252] Example 4 - Binder 4 (according to the invention)
[0253] Emulsion polymerization was carried out as described in Example 1 of the present invention, except that feed 1 did not contain 143.33 g of a 15 wt% N-hydroxymethyl methacrylamide solution (1.0 pphm), and the styrene content of feed 2 was reduced. In addition, the amount of water in feed 1 was reduced to 593.89 ml.
[0254] The solid content of the dispersion was 50.5% by weight. The glass transition temperature T g It is 6.6℃.
[0255] Analysis of polymer dispersions using HDC:
[0256] Bimodal particle size distribution:
[0257] The particle group of "smaller" particles has its maximum peak at 265 nm and the proportion fraction to the whole polymer is 80% by weight.
[0258] The particle population of "larger" particles has its maximum peak at 484 nm and the proportion fraction to the total polymer is 20% by weight.
[0259] Example 6 - Binder 6 (according to the invention)
[0260] Emulsion polymerization was carried out as described in Example 1 of the present invention, except that feed 1 did not contain 430.00 g of a 15 wt% N-hydroxymethyl methacrylamide solution (3.0 pphm), and the styrene content in feed 2 was reduced by about 1.5 pphm and the butadiene content was reduced by about 1.5 pphm. In addition, the amount of water in feed 1 was reduced to 350.22 ml.
[0261] The solid content of the dispersion was 50.5% by weight. The glass transition temperature T g is 10℃.
[0262] Analysis of polymer dispersions using analytical ultracentrifugation:
[0263] Bimodal particle size distribution:
[0264] The particle group of "smaller" particles has its maximum peak at 260 nm and the proportion fraction to the whole polymer is 50% by weight.
[0265] The particle population of "larger" particles has its maximum peak at 490 nm and the proportion fraction to the total polymer is 50% by weight.
[0266] Example 7—Binder 7 (according to the present invention)
[0267] The polymerization was carried out analogously to that described in Example 1, except that the polymerization was carried out at 90° C. The solids content of the dispersion was 50.5% by weight. The glass transition temperature T g It is 13.5℃.
[0268] Analysis of polymer dispersions using HDC:
[0269] Particle size distribution: The maximum peak is at 215nm with a tail.
[0270] Example 8—Binder 8 (according to the present invention)
[0271] The polymerization was carried out similarly to that described in Example 1, except that the polymerization was carried out at 95°C.
[0272] The solid content of the dispersion was 50.5% by weight. The glass transition temperature T gIt is 15.7℃.
[0273] Analysis of polymer dispersions using HDC:
[0274] Particle size distribution: The maximum peak is at 188nm with a tail.
[0275] Example 9 - Binder 9 (according to the present invention)
[0276] Emulsion polymerization was carried out as described in Example 1 of the present invention, except that feed 1 did not contain 71.67 g of a 15 wt% N-hydroxymethyl methacrylamide solution (0.5 pphm), and the styrene content of feed 2 was reduced. In addition, the amount of water in feed 1 was reduced to 660.60 ml.
[0277] The solid content of the dispersion was 50.5% by weight. The glass transition temperature T g It is 8.4℃.
[0278] Analysis of polymer dispersions using HDC:
[0279] Particle size distribution: The maximum peak is at 240nm with a tail.
[0280] Example 10 - Binder 10 (according to the present invention)
[0281] Emulsion polymerization was carried out as described in Example 1 of the present invention, except that feed 1 did not contain 215 g of a 15 wt% solution of N-methylol methacrylamide (1.5 pphm), and the styrene content of feed 2 was reduced. In addition, the amount of water in feed 1 was reduced to 538.77 ml ml.
[0282] The solid content of the dispersion was 50.5% by weight. The glass transition temperature T g It is 7.4℃.
[0283] Analysis of polymer dispersions using HDC:
[0284] Bimodal particle size distribution:
[0285] The particle population of "smaller" particles has its maximum peak at 281 nm and the proportion fraction to the whole polymer is 88% by weight.
[0286] The particle population of "larger" particles has its maximum peak at 435 nm and the proportion of the total polymer is 12% by weight.
[0287] Example 12—Binder 12 (Not According to the Invention)
[0288] Emulsion polymerization was carried out as described in Example 1 of the present invention, except that the polymer composition and the amount of free radical chain transfer agent were the same as those of Example 1 from EP 2869372: 61.91 pphm styrene, 33.33 pphm butadiene, 3.81 pphm itaconic acid, 0.95 pphm 2-hydroxyethyl acrylate and 0.3 pphm tert-dodecyl mercaptan.
[0289] Initial feed :
[0290] 310.38g of water
[0291] 13.47 g of a 29.7 wt% dispersion of polystyrene latex with an average particle size of 30 nm (0.20 pphm)
[0292] 30.00 g of 2 wt% EDTA solution (complexing agent) (0.03 pphm)
[0293] 1.33 g of 15 wt% sodium lauryl sulfate solution (emulsifier A) (0.01 pphm)
[0294] 4.00 g of 45 wt% sodium dodecyl diphenyl ether disulfonate (emulsifier B) (0.09 pphm)
[0295] 40.00 g of styrene (2.0 pphm)
[0296] 20.50 g of butadiene (1.0 pphm)
[0297] Add 1 :
[0298] 57.14 g of 7 wt% sodium persulfate solution (Initiator A) (0.20 pphm)
[0299] Feed 1 :
[0300] 32.00 g of 15 wt% sodium lauryl sulfate solution (0.24 pphm)
[0301] 23.11 g of 45 wt% sodium dodecyl diphenyl ether disulfonate (emulsifier B) (0.52 pphm)
[0302] 33.33 g of 15 wt% sodium hydroxide solution (0.25 pphm)
[0303] 1088.57 g of 7 wt% aqueous itaconic acid solution (3.81 pphm)
[0304] Feed 2 :
[0305] 71.81 g of 2-hydroxyethyl acrylate (0.95 pphm)
[0306] 1198.16 g of styrene (59.91 pphm)
[0307] 6.00 g of tert-dodecyl mercaptan (0.3 pphm)
[0308] Feed 3 :
[0309] 646.6 g of butadiene (32.33 pphm)
[0310] Feed 4 :
[0311] 234.29 g of 7 wt% sodium peroxodisulfate solution (0.82 pphm)
[0312] Feed 5 :
[0313] 70.00 g of 10 wt% tert-butyl hydroperoxide (Initiator B) solution (0.35 pphm)
[0314] Feed 6 :
[0315] 75.18 g of 13.1 wt% acetone bisulfite solution (0.53 pphm)
[0316] Feed 7 :
[0317] 97.33 g of 15 wt% sodium hydroxide solution (0.73 pphm)
[0318] The components of the initial charge were charged to a 6 l pressure reactor and mixed. The initial charge was heated to 85° C. When 85° C. was reached, initiator A (charge 1) was added within 5 minutes and polymerization was started. The mixture was stirred for a further 5 minutes.
[0319] Feeds 1, 2, 3 and 4 were then started immediately (time: 0 minutes) and the temperature was continuously reduced to 80° C. over a period of 20 minutes. Feeds 1, 2 and 4 were completed over a period of 6 hours. Feed 3 was completed over a period of 5 hours and 30 minutes.
[0320] After the end of the metered addition of feeds 1, 2 and 4, the polymerization mixture was stirred for a further 30 minutes. 287 ml of water (14.33 pphm) were then added.
[0321] Feeds 5 and 6 were then started and completed over a period of 90 minutes. Feed 7 was started 15 minutes before the end of feeds 5 and 6 and completed over a period of 15 minutes. After the end of feeds 5, 6 and 7, the polymerization mixture was cooled to room temperature.
[0322] The solid content of the dispersion was 48.5% by weight. The glass transition temperature T g is 9℃.
[0323] Analysis of polymer dispersions using HDC:
[0324] Particle size distribution: The maximum peak is at 217 nm, showing a shoulder in the lower nm range.
[0325] Example 13 - Binder 13 (not according to the invention)
[0326] Emulsion polymerization was carried out as described in Comparative Example 1, except that Feed 2 contained 100 g acrylonitrile (5 pphm) and the styrene content of Feed 2 was reduced.
[0327] The solid content of the dispersion was 48.5% by weight. The glass transition temperature T g is 15℃.
[0328] Analysis of polymer dispersions using HDC:
[0329] Particle size distribution: Maximum peak at 199 nm, showing shoulders in the lower nm range.
[0330] Table 1: Monomer compositions of binders B1-B13 (B2, B12 and B13 are not according to the invention)
[0331]
[0332] B2, B12 and B13 are not according to the present invention
[0333] AS: Acrylic
[0334] Mamol: N-hydroxymethyl methacrylamide
[0335] HEA: Hydroxyethyl Acrylate
[0336] Preparation of polymer films
[0337] A film with a theoretical thickness of 0.5 mm was prepared by pouring the dispersion into a silicone mold. The film was dried and peeled off at room temperature for 18 hours. The extracted film was dried in a 60°C drying oven for 2 hours. The film was then stored at 40°C for 2 hours and at 70°C for 2 hours.
[0338] For electrolyte immersion, a film with a theoretical thickness of 0.5 mm was prepared by pouring the dispersion into a silicone mold. The film was dried and peeled off at room temperature for 18 hours. The extracted film was dried in a 60°C drying oven for 2 hours. The film was then stored at 40°C for 2 hours and at 70°C for 2 hours, and finally stored at 70°C for 3 days in LP57 electrolyte (1M LiPF6 ethylene carbonate: methyl ethyl carbonate, 3:7).
[0339] Mechanical characterization of polymer films
[0340] Breaking stress and breaking elongation (stress / strain measurement)
[0341] The polymer films were characterized in quasi-static tensile tests until polymer failure.
[0342] Preparation of samples: Test specimens were prepared from the obtained polymer films using a punching process. For punching, a shoulder bar shape was used for a test specimen geometry of 75 mm in length according to DIN 53504. A dumbbell shape (according to DIN 54504 S2) was used for a test specimen geometry of 75 mm × 4 mm in size. The thickness of the test specimen was obtained from the average of 3 measurements. Afterwards, the test specimens were tested after storage for 15 hours at 23° C. and 50% relative air humidity in a climate chamber.
[0343] Test execution :
[0344] The tensile test was carried out on a Zwick 110846 testing machine. The specimen was clamped into the machine with a test track of 40 mm. The pulling speed was 200 mm / min. The stress and strain values were output by the testing machine.
[0345] Table 2: Stress / strain of neat polymer dispersion films after storage at 40°C for 2 hours and then at 70°C for 2 hours By storing at 40 ° C for 2 hours, storing at 70 ° C for 2 hours, and then in LP57 electrolyte (1MLiPF6 carbonate Ethylene carbonate:ethyl methyl carbonate, 3:7) was stored at 70°C for 3 days and an additional electrolyte soak was performed. .
[0346]
[0347] ret.: reserved;
[0348] DEC: Diethyl carbonate good stress level ≥8N / mm 2
[0349] Good strain value ≥300%
[0350] Good strain value according to electrolyte immersion: ≥200%
[0351] Good stress values after electrolyte soaking show retention of at least 60% of the initial value.
[0352] The binder polymers according to the invention exhibit good stress / strain behavior. They retain high stress values even after electrolyte immersion.
[0353] Preparation of anode slurry
[0354] Components used:
[0355] Texturecell TM 2000PA 07IFF granular carboxymethyl cellulose (CMC) (average molecular weight 450 mol / g-500 kmol / g, 2000 mPas viscosity of 2% aqueous solution and degree of substitution 0.7)
[0356] Carbon black Timcal Super C65 from Imerys (BET = 62m 2 / g)
[0357] Artificial graphite SMG A5 from Showa Denko (particle size D10 = 7.6 μm, D50 = 18.5 μm, D90 = 33.5 μm, BET von 3.0 μm 2 / g,
[0358] Low-cost silicon oxide KSC 1265 from the company Shin-Etsu (Japan) (non-lithium-doped SiOx type particle size D10 = 4.1 μm, D50 = 6.5 μm, D90 = 9.3 μm)
[0359] A 2 wt% aqueous solution of carboxymethylcellulose was prepared and stored for 24 hours.
[0360] To prepare the anode slurry, the 2 wt % carboxymethyl cellulose solution was provided, degassed several times while applying a slight vacuum (300 mbar) and stirred at 2000 rpm for 30 minutes with a dissolving stirrer. Subsequently, soot was dosed, a slight vacuum (300 mbar) was applied again and dispersed at a speed of 3500 rpm. Subsequently, 4 parts of graphite were first dosed and then 4 parts of SiOx were dosed. After the solids were dosed, a slight vacuum (300 mbar) was dispersed (speed 3500 rpm). The polymer dispersions of each example were then stirred at 500 rpm for 10 minutes and then at 150 rpm for 10 minutes during the degassing process (under a vacuum of 300 mbar). Finally, the solids content was set to a value in the range of 48%-50%.
[0361] Table 3: Slurry composition
[0362] Components Solid content (weight %) Graphite Hitachi SMG A5 83.5 SiOx Shin-Etsu KSC1265 9.5 Conductive additive carbon black—Super C65 (Imerys) 1.3 CMC (CRT 2.000PA 07 (2.0% solution) IFF) 1.7 Binder 4
[0363] Preparation of silicon-containing anode according to the invention
[0364] The corresponding anode slurry was applied to a copper sheet (250 mm x 150 mm) (manufacturer, thickness: 10 μm) with a doctor blade at a gap size of 250 μm. The coated anode was then dried at 60° C. for 2 minutes and at 120° C. for 1 minute. Subsequently, the coated copper sheet was calendered to a thickness of 1.45 g / cm 3 The density of (target density).
[0365] Finally, the coated copper sheets were stored in a climate chamber at 23 °C and 50% humidity for 24 h before mechanical characterization.
[0366] Mechanical Characterization of Silicon-Containing Anodes Using the 90° Peel Test
[0367] Sample preparation :
[0368] The coated copper sheet was cut into strips 25 mm wide and 150 mm long. HDPE specimens (20×3 cm 2 ) as carrier material. Double-sided adhesive tape was applied to the carrier material. The coated anode strip was placed on the adhesive strip and pressed with a rubber roller (without force), wherein the coated side was free of bubbles. Subsequently, the layers were combined together in a defined manner by rolling a 2 kg hand roller twice on the composite without force. The samples prepared in this way were stored in a climate chamber at 23° C. and 50% humidity for 24 hours.
[0369] The test was performed on a Zwick tearing machine.
[0370] Test Parameters :
[0371] Device: Zwick tearing machine
[0372] Trigger angle: 90°
[0373] Measuring speed: 50mm / min
[0374] Preload: 0.1N
[0375] Clamping length: 20mm
[0376] Measuring distance: 60mm
[0377] Estimated value: 10mm-50mm
[0378] Rating N / m
[0379] Table 4: Peel strength values of slurry coatings .
[0380]
[0381] The coatings with the adhesive according to the invention have a peel strength of ≥15 N / m.
Claims
1. Use of an aqueous dispersion of a polymer P obtainable by free radical initiated emulsion polymerization as a polymer binder in an electrode slurry composition for a secondary battery anode, the emulsion polymerization comprising polymerizing the following at a polymerization temperature in the range of 70° C. to 95° C.: (a) 40 to 75 parts by weight of at least one vinyl aromatic compound, (b) 22.5 to 55 parts by weight of at least one conjugated aliphatic diene, (c) 0.5 to 10 parts by weight of at least one ethylenically unsaturated monomer containing an acid group (d1) 1 to 5 parts by weight of acrylamide and / or methacrylamide, (d2) 1 to 10 parts by weight of acrylonitrile and / or methacrylonitrile (e) 0 to 5 parts by weight of a monoethylenically unsaturated monomer having at least one epoxy, hydroxyl, N-methylol or carbonyl group (f) 0 to 20 parts by weight of at least one other monoethylenically unsaturated monomer, The total amount of the monomers (a) to (f) is 100 parts by weight.
2. The use according to claim 1, wherein monomer (e) is selected from the group consisting of N-methylol acrylamide and N-methylol methacrylamide.
3. The use according to any one of claims 1 and 2, wherein the polymer P is obtainable by free radical initiated emulsion polymerization comprising polymerizing: (a) 45 to 68.9 parts by weight of at least one vinyl aromatic compound (b) 28 to 50 parts by weight of at least one conjugated aliphatic diene (c) 1 to 8 parts by weight of at least one ethylenically unsaturated carboxylic acid (d1) 1 to 3 parts by weight of acrylamide (d2) 1 to 8 parts by weight of acrylonitrile (e) 0.1 to 4 parts by weight of a monoethylenically unsaturated monomer having at least one N-methylol group and (f) 0 to 15 parts by weight of at least one other monoethylenically unsaturated monomer, The amounts of the monomers (a) to (f) are 100 parts by weight in total.
4. Use according to any one of claims 1 to 3, wherein the polymer P is obtainable by free-radically initiated emulsion polymerization comprising polymerization at a polymerization temperature in the range of 75°C to 90°C.
5. Use according to any one of claims 1 to 4, wherein the polymer P is obtainable by free-radically initiated emulsion polymerization, the emulsion polymerization comprising polymerization in the presence of a seed latex.
6. The method according to claim 1, wherein the polymer P is obtainable by free-radically initiated emulsion polymerization, comprising polymerization in the presence of ≤ 1 part by weight of a free-radical chain transfer agent, based on 100 parts by weight of total monomers.
7. The use according to any one of claims 1 to 6, wherein the polymer P has a molecular weight of at least 8 N / mm 2 The stress at break and the strain is at least 150%, as described herein.
8. An electrode slurry composition for an anode, comprising an anode active material, a conductive material, a co-binder, a dispersion medium and the polymer P according to any one of claims 1 to 7.
9. The electrode slurry composition for an anode according to claim 8, wherein the electrode slurry composition for an anode comprises a dispersion medium and 0.5 to 20% by weight of polymer P, 50 wt % to 98 wt % of anode active material, 0.01 wt % to 20 wt % of a conductive material, 0.5 wt % to 20 wt % co-binder.
10. A method for preparing a secondary battery anode, the method comprising the following steps: (a) combining the anode active material, the conductive material, the co-binder, the dispersion medium and the aqueous dispersion of the polymer P according to any one of claims 1 to 7 into an electrode slurry composition (b) Providing a current collector (c) coating the current collector with the electrode slurry composition (d) drying the coated collector and (e) Optionally molding the coated collector. 11 . A secondary battery anode formed by applying the electrode slurry composition for an anode according to claim 8 or 9 to a current collector and drying the negative electrode slurry composition. 12 . A lithium ion secondary battery, comprising the secondary battery anode according to claim 9 .
13. An aqueous dispersion of a polymer P according to any one of claims 1 to 7, obtainable by free-radical initiated aqueous emulsion polymerization comprising polymerizing at a polymerization temperature in the range of 70°C to 95°C: (a) 40 to 75 parts by weight of at least one vinyl aromatic compound, (b) 22.5 to 55 parts by weight of at least one conjugated aliphatic diene, (c) 0.5 to 10 parts by weight of at least one ethylenically unsaturated monomer containing an acid group (d1) 1 to 5 parts by weight of acrylamide and / or methacrylamide, (d2) 1 to 10 parts by weight of acrylonitrile and / or methacrylonitrile (e) 0 to 5 parts by weight of a monoethylenically unsaturated monomer having at least one epoxy, hydroxyl, N-methylol or carbonyl group (f) 0 to 20 parts by weight of at least one other monoethylenically unsaturated monomer, wherein the amount of the monomers (a) to (f) totals 100 parts by weight.
14. A process for preparing an aqueous dispersion of a polymer P according to any one of claims 1 to 7 by free-radically initiated aqueous emulsion polymerization, the process comprising free-radically polymerizing in an aqueous medium at a polymerization temperature in the range of 70° C. to 95° C.: (a) 40 to 75 parts by weight of at least one vinyl aromatic compound, (b) 22.5 to 55 parts by weight of at least one conjugated aliphatic diene, (c) 0.5 to 10 parts by weight of at least one ethylenically unsaturated monomer containing an acid group (d1) 1 to 5 parts by weight of acrylamide and / or methacrylamide, (d2) 1 to 10 parts by weight of acrylonitrile and / or methacrylonitrile (e) 0 to 5 parts by weight of a monoethylenically unsaturated monomer having at least one epoxy, hydroxyl, N-methylol or carbonyl group (f) 0 to 20 parts by weight of at least one other monoethylenically unsaturated monomer, wherein the amount of the monomers (a) to (f) totals 100 parts by weight.
Citation Information
Patent Citations
Aq copolymer dispersions with low free monomer content
DE4419518A1
Method for the production of an aqueous polymer dispersion
DE4435422A1
Uniform redn. of residual concn. of different monomers in aq. polymer dispersion
DE4435423A1
Heterogeneous polymer latex of relatively hard and relatively soft interpolymers of a monovinylidene aromatic monomer and an aliphatic conjugated diene monomer and paper coating compositions containing said latexes
EP0040419A2
Aqueous polymer dispersions
EP0567812A1